2006
DOI: 10.1159/000097667
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glucose Uptake and Metabolism in Mesangial Cells Overexpressing Glucose Transporter 1 Increases Interleukin-6 and Vascular Endothelial Growth Factor Production: Role of AP-1 and HIF-1α

Abstract: Previous results indicate that enhanced glucose transporter (GLUT)1 expression mediates the deleterious effects of metabolic and hemodynamic perturbations leading to diabetic kidney disease. First screening for altered gene expression in GLUT1 overexpressing cells (GT1) by Affymetrix microarray analysis revealed upregulation of interleukin-6 (IL-6) and vascular endothelial growth factor (VEGF) expression, which was verified by RT-PCR. Subsequently, IL-6 and VEGF protein production was more than 3-fold increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…9, the same system that was used by Lee et al for their transient experiments. Such suppression in mTOR activity occurred because reduced GLUT1 levels led to a reduction in glucose utilization, independent of extracellular glucose concentration (11,34), and thereby enhanced Rheb association with GAPDH, reduced Rheb association with mTOR, and inhibited mTOR activation. This presumably protective response did not occur in mesangial cells that were the focus of most of our experiments, nor does it occur in glomeruli in rodent models of diabetic nephropathy (5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9, the same system that was used by Lee et al for their transient experiments. Such suppression in mTOR activity occurred because reduced GLUT1 levels led to a reduction in glucose utilization, independent of extracellular glucose concentration (11,34), and thereby enhanced Rheb association with GAPDH, reduced Rheb association with mTOR, and inhibited mTOR activation. This presumably protective response did not occur in mesangial cells that were the focus of most of our experiments, nor does it occur in glomeruli in rodent models of diabetic nephropathy (5).…”
Section: Discussionmentioning
confidence: 99%
“…The KRP buffer was removed and replaced with 0.1 mM unlabeled 2-DOG (Sigma) and 0.5 Ci/ml 3 H-2-DOG (Perkin Elmer, Waltham, MA) in KRP buffer ϩ 1% (wt/vol) BSA Ϯ 20 nM cytochalasin B, an irreversible inhibitor of glucose transport, at 37°C for 5 min. Previous studies showed that uptake is linear for at least 10 min in the control MC line (34). The plates were subsequently washed twice for 5 min each time with cold KRP solution containing 200 M phloretin to quench 2-DOG uptake.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…40 In addition, we specified the mechanistic role of HCV core in the course of the hepatic angiogenesis, during HCV infection.…”
Section: Discussionmentioning
confidence: 99%